2020
DOI: 10.1097/hs9.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Absence of JAK2V617F Mutated Endothelial Colony‐Forming Cells in Patients With JAK2V617F Myeloproliferative Neoplasms and Splanchnic Vein Thrombosis

Abstract: P hiladelphia (Ph)-negative myeloproliferative neoplasms (MPN) are acquired hematologic diseases with increased production of mature blood cells. They include polycythemia vera (PV), essential thrombocythemia (ET) and myelofibrosis (MF). The most frequent molecular abnormality found in Ph negative MPN is JAK2V617F, an activating mutation of JAK2 which is responsible for constitutive signaling of various cytokine receptors. Arterial and venous thromboses are the main complications of these diseases and are resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The absence of the JAK2 mutation in ECFC from MPN patients was recently confirmed by Guy and colleagues. 13 Teofili et al 12 however, reported that ECFC from patients with MPN were JAK2 V617F + ( Figure 1 ). Almost half of the MPN patients studied were reported to have MPN-like genetic abnormalities in their ECFC, including either SOCS gene hypermethylation or the presence of JAK2 V617F.…”
Section: Jak2 V617f-positive Endothelial Cells In Patients With Myeloproliferative Neoplasms ( Figure 1 )mentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of the JAK2 mutation in ECFC from MPN patients was recently confirmed by Guy and colleagues. 13 Teofili et al 12 however, reported that ECFC from patients with MPN were JAK2 V617F + ( Figure 1 ). Almost half of the MPN patients studied were reported to have MPN-like genetic abnormalities in their ECFC, including either SOCS gene hypermethylation or the presence of JAK2 V617F.…”
Section: Jak2 V617f-positive Endothelial Cells In Patients With Myeloproliferative Neoplasms ( Figure 1 )mentioning
confidence: 99%
“…This concept and its implications remain controversial and its significance has been questioned by some investigators. 9 , 11 , 13 The aim of this review is to analyze this evidence in a critical fashion and assess the validity of the link between EC and MPN pathobiology.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, JAK2 V617F is not restricted to hematopoietic cells; it is also likely to be present in the endothelial cells of the liver and spleen, thereby promoting the expression of endothelial P-selectin and contributing to thrombosis [23,24]. However, the expression of JAK2 in endothelial cells within the liver has yet to be definitively confirmed [25].…”
Section: Mpns: Driver and Additional Mutationsmentioning
confidence: 99%
“…Thus, depending on the specific microenvironment in MPNs, JAK2V617F + ECs may support anti-thrombotic or pro-thrombotic effects in MPN [ 97 ]. Nevertheless, just recently, Guy et al were not able to detect the JAK2 V617F mutation in PB-derived ECs of two MPN patient cohorts (DNA of 12/31 patients was analyzed), potentially demonstrating a lack of reproducibility of endothelial colony-forming cell (ECFC) cultivation techniques [ 98 ].…”
Section: Inflammatory Conditions In the Hematopoietic Niche Beforementioning
confidence: 99%